An analysis of axisymmetric receding contacts - Da Ponte Lopes, J (2020)
Bolted joints are one of the most used types of fixture in industry and when the contact area is small compared with the joint’s thickness, they represent an example of receding contacts, which are characterised by the reduction of the contact area when a loading is applied. Despite their ubiquity, axisymmetric receding contacts are not fully understand, and the current literature on the problem is limited either to plane problems or to frictionless cases.